Pengaruh Paparan Sinar UV terhadap Ketahanan Warna Hasil Cetak DTF pada Kain Cotton 30s dan Spandek Rayon - Nabila Dwi Julyanti; Emmidia Djonaedi; Rachmah Nanda Kartika (Pusat riset dan Inovasi Nasional, 2025)
Color fastness in Direct to Film (DTF) digital screen printing is influenced by various external factors, one of which is exposure to ultraviolet (UV) light. This study aims to evaluate the impact of UV light on the color stability of DTF prints on two types of fabric, namely 30s cotton and spandex rayon. A quantitative approach was used in this study, involving color difference testing (ΔE), washing simulations, and UV exposure. Based on the analysis results, cotton 30s demonstrated superior color fastness performance compared to spandex rayon, as indicated by lower ΔE values after UV exposure and washing processes. Conversely, spandex rayon experienced more drastic color changes, especially after being washed with bleach detergent. These findings emphasize that the selection of fabric materials and washing methods are critical factors.